2020
DOI: 10.1002/nop2.580
|View full text |Cite
|
Sign up to set email alerts
|

Research on the individualized short‐term training model of nurses in emergency isolation wards during the outbreak of COVID‐19

Abstract: COVID-19 is an acute infectious pneumonia, which is a respiratory disease caused by a new coronavirus infection symptom, may combined with mild dry cough, fatigue, poor breathing, diarrhoea and other symptoms, catarrh and other symptoms such as runny nose and sputum are rare (National Health Commission of China). Respiratory droplets and contact transmission are the main

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…Our search strategy produced a total of 5128 articles from all the databases. After the screening process, 21 articles ( Aiello et al, 2011 ; Albott et al, 2020 ; Bansal et al, 2020 ; Blake et al, 2020 ; Buselli et al, 2020 ; Cai et al, 2020 ; Chen et al, 2006 ; Cheng et al, 2020 ; Cheung et al, 2020 ; Cole et al, 2020 ; Donnelly et al, 2020 ; Robert E. Feinstein et al, 2020 ; Gonzalez et al, 2020 ; Hong et al, 2020 ; Maunder et al, 2003 , 2010 ; Ping et al, 2020 ; Schreiber et al, 2019 ; Sockalingam et al, 2020 ; Waterman et al, 2018 ; Zhou et al, 2020 ) were eligible to be included in the systematic review ( Figure 1 ). Through the hand-search of the latter, three additional articles ( Geoffroy et al, 2020 ; Giordano et al, 2020 ; Khee et al, 2004 ) were identified and included.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our search strategy produced a total of 5128 articles from all the databases. After the screening process, 21 articles ( Aiello et al, 2011 ; Albott et al, 2020 ; Bansal et al, 2020 ; Blake et al, 2020 ; Buselli et al, 2020 ; Cai et al, 2020 ; Chen et al, 2006 ; Cheng et al, 2020 ; Cheung et al, 2020 ; Cole et al, 2020 ; Donnelly et al, 2020 ; Robert E. Feinstein et al, 2020 ; Gonzalez et al, 2020 ; Hong et al, 2020 ; Maunder et al, 2003 , 2010 ; Ping et al, 2020 ; Schreiber et al, 2019 ; Sockalingam et al, 2020 ; Waterman et al, 2018 ; Zhou et al, 2020 ) were eligible to be included in the systematic review ( Figure 1 ). Through the hand-search of the latter, three additional articles ( Geoffroy et al, 2020 ; Giordano et al, 2020 ; Khee et al, 2004 ) were identified and included.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the included articles reported interventions implemented in China (20.8%) ( Cai et al, 2020 ; Cheng et al, 2020 ; Cheung et al, 2020 ; Hong et al, 2020 ; Zhou et al, 2020 ) and Canada (16.7%) ( Aiello et al, 2011 ; Maunder et al, 2003 , 2010 ; Sockalingam et al, 2020 ), followed by USA ( Albott et al, 2020 ; Robert E. Feinstein et al, 2020 ; Gonzalez et al, 2020 ) and UK ( Blake et al, 2020 ; Cole et al, 2020 ; Donnelly et al, 2020 ) (12.6%, respectively). The rest of the articles referred to Italy ( Buselli et al, 2020 ; Giordano et al, 2020 ) and Africa ( Schreiber et al, 2019 ; Waterman et al, 2018 ) (8.4%, respectively), and Taiwan ( Chen et al, 2006 ), Singapore ( Khee et al, 2004 ), Malaysia ( Ping et al, 2020 ), France ( Geoffroy et al, 2020 ), Spain ( Mira et al, 2020 ) (4.1%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations